Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 74. Beitrag. Coleoptera: Nachtrag zum 48. Beitrag mit Beschreibung von zwei neuen Cyphon-Arten (Dascillidae, Helodidae). - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 1969)
Further material is added for Dascillus cervinus Linne (13 individuals from 6 sites in Albania). Cyphon friesei sp. n. is described from Albania (given as Cyphon spec. in the 48th contribution), and Cyphon jelineki sp. n. is described from Yugoslavia. Nomenclatural Actsfriesei Klausnitzer, 1969 (Cyphon), spec. n.jelineki Klausnitzer, 1969 (Cyphon), spec. n.